NUCLEAR THREAT DURING THE COVID-19 PANDEMIC - Обіход, Тетяна Вікторівна; Біленчук, Петро Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to analyze the socio-economic consequences of the COVID-19 pandemy for the world community and for the Ukrainian community in particular. Methods: comparative legal analysis, cognitive-analytical, data collection systems, etc. Results: some sectors of the economy have been identified, at which in Ukraine should be paid attention to in today’s conditions; the main conclusions on nuclear safety are presented. Discussion: the necessity of a systematic approach to nuclear safety in the conditions of coronary crisis is substantiated. When the world announces an unprecedented pandemic and the onset of a global economic crisis, a sober and timely approach to all aspects of life in the Ukrainian community is needed. Against the background of unemployment around the world and in Ukraine in particular, it is necessary to pay special attention to the agro-industrial sector of Ukraine. Here, the distance will be maintained between employees, and earnings will be stable. It is only necessary to set up small processing plants near the fields and gardens. The development is quite possible by accelerating of procurement and processing in agricultural service cooperation. It is emphasized that the Middle East controversy, North Korean nuclear weapons, the US-Iran conflict, the Sino-US trade and economic wars and other problems have only fueled tensions. Therefore, the coronavirus played only the role of a simple trigger of re-globalization. The analysis of the current political situation leads to the need to control the illicit trafficking of nuclear and other radioactive materials and to increase criminal liability in order to prevent incidents related to nuclear safety.